The suspension of the act claimed to “contrario sensu” of the Amparo trial (Revista de Investigaciones Universidad del Quindío, 2021)
This document sets out the suspension of the act claimed as the Procedural Institution that it is, its importance and significance, whose purpose is to keep alive the matter that gives rise to the Amparo Trial, freezing the actions of the Authority, ensuring that Constitutional protection is achieved. This figure allows the Judge to keep things in the state in which they are, by incidental means; thereby limiting the actions of the authorities to guarantee the protection of human rights. What happens when the failure of the Authority endangers the matter of the Amparo? In this sense, the case of an elderly man living in very precarious conditions of poverty and marginalization is documented, who was granted a suspension a Contrary Sensu so that the responsible authority could provide him with the necessary medical services. The cases in which the Amparo Judge dictates conservation measures and orders the authorities to continue with the exercise of their jurisdictional powers in order to achieve the broadest protection of human rights are described.
Keywords: Claimed act; constitutionality of the claimed act; protection; protection matter; social interest; suspension